Cardiogenic shock with 1° heart block after organophosphorus poisoning: A case report and review of cardiac complication in organophosphorus poisoning - Manoj Lakhotia; Hans Raj Pahadiya; Harish Kumar; Sangappa Ravi Jainapur; Akanksha Choudhary (Wolters Kluwer Medknow Publications, 2015)
Organophosphorus (OP) compounds have been widely used as pesticide in India. Because of wide use and easy availability, it is the most common poisoning. OP compound poisoning can lead to cardiac complications. Here we report a case of 26-year-old female who presented after ingestion of unknown quantity of chlorpyrifos. She had cardiogenic shock, 1° heart block with prolonged QTc interval, and sinus bradycardia. She recovered completely after treatment with atropine and pralidoxime.